How we manage patients with Waldenström macroglobulinaemia. (10th April 2018) - Simon, Laurence; Baron, Marine; Leblond, Véronique
Summary: Waldenström macroglobulinaemia (WM) is a rare, indolent B‐cell lymphoproliferative disorder characterized by cellular involvement in bone marrow and monoclonal IgM production. Symptoms can be related to cytopenias, tumoural involvement, or IgM‐related disorders. Somatic mutations in the MYD88 gene have been described in the majority of WM cases. The mutation is responsible for a gain‐of‐function and induces activation of nuclear factor‐κB, for DNA transcription and cell survival. It seems that MYD88 mutation is associated with better prognosis and better response to some treatment. Treatments are started when WM is symptomatic, following systematic biological and morphological assessments. Therapeutic choice depends on age, frailty and urgent efficacy need. In first line, the majority of patients are treated with monoclonal anti‐CD20 antibody‐based regimens combined with cytotoxic chemotherapy. Rituximab, cyclophosphamide and dexamethasone remain the most commonly used regimen with good safety. Nevertheless, increasing numbers of new drugs are becoming available or are in development. Proteasome inhibitors, such as bortezomib or carfilzmib, showed good and rapid responses. Bruton tyrosine kinase (BTK) inhibitor demonstrated excellent results and is now available for relapse/refractory disease or as first line for some patients. This review highlights the diagnostic procedures and therapeutic approaches in WM.